PENERAPAN DIGITAL MARKETING SEBAGAI SISTEM INFORMASI MANAJEMEN PADA PENERIMAAN PESERTA DIDIK BARU DI SEKOLAH SWASTA KOTA BANDUNG - Rahmawati, Ami; Hidayati, Dian (Academy of Education Journal, 2023)
Digital marketing is a marketing strategy using digital media and the internet through branding. In the current digital era, information dissemination is easy to reach widely, but for the world of education which has a level of competitive competition, digital marketing has not been fully utilized, although several private schools in the city of Bandung have generally carried out publications and promotions on social media accounts, but still in the form of updating information not yet to marketing, especially during the new student admissions period, it was seen that the empowerment of digital platforms was still weak. The purpose of this research is to find out to what extent digital marketing is utilized during the admission period for new students at private schools in Bandung, the method used in this study uses a qualitative data analysis model through the Case Study approach where the data obtained will be processed into a solution in implementing digital marketing in private school.